Analysis of supply interruptions by disconnections of transformers of power - Ibarcena Vega, Alfredo (2024)
Operation is a fundamental process for companies engaged in power transmission, especially when it comes to the operation of power transformers, which are one of the main components of the electric power system and represent a large part of the investment required to implement these systems. To improve the quality of the operation of power transformers and ensure their reliability and safety, it is essential to monitor power supply interruptions and the electrical parameters that comprise them. Therefore, the objective of this research is to improve operating practices to minimize the impact of power supply interruption events on the consumer due to disconnections of 22.9 kV, 60 kV, 138 kV and 550 kV power transformers operated and maintained by ISA REP, one of the largest electric transmission companies in Peru. The results of this study, i.e. the analysis of technical operating indicators over 4 years (from 2018 to 2021), the review of the documentation of the company's operating practices in force during this period and the proposal of best operating practices based on the previous results, aiming to improve the operation of the transmission system, are expected to contribute to the knowledge of this field of electrical engineering.